2019
DOI: 10.1111/ced.14127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response rate and flares of hidradenitis suppurativa in the treatment with adalimumab

Abstract: Background. Hidradenitis suppurativa/acne inversa (HS) is a chronic, inflammatory, skin disease. adalimumab is the sole approved drug for the treatment of HS, but it only partially controls the symptoms. Aim. To evaluate the incidence of flares during 108 weeks of therapy and the clinical response to adalimumab. Methods. In total, 20 patients with moderate-severe HS treated with adalimumab were included to evaluate the number of flares, mean time interval between flares, lesion count number of patients who rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Biologic agents were mostly prescribed for patients with Hurley stage III (31.7%). Adalimumab and infliximab are effective in the treatment of moderate‐to‐severe HS 22,23 . Consistent with current evidence, adalimumab was the most commonly used biologic therapy in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Biologic agents were mostly prescribed for patients with Hurley stage III (31.7%). Adalimumab and infliximab are effective in the treatment of moderate‐to‐severe HS 22,23 . Consistent with current evidence, adalimumab was the most commonly used biologic therapy in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our results show high response rates to adalimumab in agreement with previous research on adalimumab real‐life use 35,36 , Table 4. Other studies showed lower adalimumab effectiveness 37,38 . These differences might be explained by different sociodemographic and clinical characteristics and different outcome measures.…”
Section: Discussionmentioning
confidence: 91%
“…1 It is known from literature that fistulas are poorly responsive to the currently available medical treatments. 6,[9][10][11][12][13][14] At the same time, these lesions play a central role in the "window of opportunity" acting as a sort of watershed between medical and surgical approach. 6 Therefore, the analysis of their features related to their clinicalsonographic response may indicate when the medical therapy alone might be still effective.…”
Section: Discussionmentioning
confidence: 99%
“…It is known from literature that fistulas are poorly responsive to the currently available medical treatments 6,9‐14 . At the same time, these lesions play a central role in the “window of opportunity” acting as a sort of watershed between medical and surgical approach 6 .…”
Section: Discussionmentioning
confidence: 99%